Des enabled fingerprint system - Gobinath, Subramaniam; Kalyani, Subramanian; Senthil, Raja Balakrishnan; Baskaran, Kaliaperumal (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.